Long-term multidrug- and rifampicin-resistant tuberculosis treatment outcome by new WHO definitions in Germany. Issue 5 (24th November 2022) - Otto-Knapp, Ralf; Häcker, Brit; Krieger, David; Stete, Katarina; Starzacher, Katharina; Maier, Christina; Heyckendorf, Jan; Avsar, Korkut; Suárez, Isabelle; Rybniker, Jan; Bauer, Torsten; Günther, Gunar; et al.
Multidrug- and rifampicin-resistant tuberculosis (MDR/RR-TB) are growing threats to the goals of the END TB Strategy [1], causing substantial suffering and overwhelming costs for affected patients and families. Global treatment success for MDR/RR-TB is insufficient at only 59%. Germany has a low tuberculosis incidence (5.0 per 100 000) with 2.7% MDR-TB cases. Although resources are available, treatment success for these patients remains below World Health Organization (WHO) targets, according to national surveillance data [2]. However, long-term treatment outcomes are not systematically captured. Long-term outcomes of MDR/RR-TB with 3-year follow-up show 62% favourable outcomes in Germany. 26% were lost to follow-up or transferred. It was possible to categorise 95% of favourable outcomes as cured using the 2021 WHO outcome definitions. https://bit.ly/3bJnvfR